Experimental evidence for hypercoordination in triorganotelluronium halides with 2-(Me2NCH2)C6H4 groups12. (4th July 2019) - Beleagă, Anca; Denes, Eleonora; Silvestru, Cristian; Silvestru, Anca
Abstract : Triorganotelluronium halides of type [2-(Me2 NCH2 )C6 H4 n Ph3− n Te] + X − ( n = 1–3, X = Cl, Br, I) were prepared and structurally characterized both in solution and in the solid state, showing a ( C, N )-chelating behavior of the 2-(Me2 NCH2 )C6 H4 groups. Abstract : Heteroleptic triorganotelluronium chlorides of the type [RPh2 Te] + Cl − (1 ) and [R2 PhTe] + Cl − (4 ) [R = 2-(Me2 NCH2 )C6 H4 ] were obtained by reacting Ph2 TeCl2 with RLi in 1 : 1 and 1 : 2 molar ratios. The reaction of TeCl4 with RLi (a 1 : 3 molar ratio) afforded a mixture of [R3 Te] + Cl − (7 ) and [R2 Te(OH)] + Cl − (10 ) after separation by column chromatography. Halogen exchange reactions using KX resulted in the corresponding [RPh2 Te] + X − [X = Br (2 ), I (3 )], [R2 PhTe] + X − [X = Br (5 ), I (6 )] and [R3 Te] + X − [X = Br (8 ), I (9 )]. The compounds were characterized by multinuclear NMR spectroscopy and mass spectrometry. The NMR spectra are similar for each series of triorganotelluronium halides (1–3, 4–6 and7–9, respectively) and no clear evidence for N→Te interactions in solution could be concluded at room temperature, except in the case of compounds4–6 for which the 1 H resonance of the C H 2 N protons in the pendant arms appears as an AB spin system. For compounds7 and10 the low temperature 1 H and 13 C NMR spectra are consistent with intramolecularly coordinated pendant arms. The solid state structures for compounds1, 1 ·0.5CH2 Cl2, 3, 4 ·H2 O, 5 ·H2 O, 6, 7 ·H2 O and10 were determined by single-crystal X-ray diffraction. For all compounds the nitrogen atom of a pendant arm is involved in an intramolecular N→Te interaction in the range 2.571(3)–2.839(8) Å. This results in hypercoordinated triorganotelluronium(iv ) cations with different distorted coordination geometries: "see saw" in1–3, square pyramidal in4–6 and10, and octahedral in7 . Further secondary interactions between cations, anions and water molecules were observed in the crystals of these species, resulting in different supramolecular associations.